2023
DOI: 10.1021/acsomega.3c02586
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Peel Phytochemistry, Pharmacological Properties, Methods of Extraction, and Its Application: A Comprehensive Review

Jyoti Singh,
Hamita Preet Kaur,
Anjali Verma
et al.

Abstract: Pomegranate peel, derived from the processing of Punica granatum L. (pomegranate), has traditionally been considered agricultural waste. However, recent studies have revealed its potential as a rich source of bioactive compounds with diverse pharmacological effects. Pomegranate peel is a rich reservoir of antioxidants, polyphenols, dietary fiber, and vitamins, which contribute to its remarkable bioactivity. Studies have demonstrated the anti-inflammatory, cardioprotective, wound healing, anticancer, and antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…In this context, several research studies, published in the last 20 years ( Singh et al, 2023 ), highlighted that the fruit of the pomegranate, Punica granatum L. , possesses various pharmacological properties including antioxidant, anti-inflammatory, anti-cancer, and antimicrobial activities. Furthermore, PPE is a nutrient by-product of the fruit that is becoming abundant due to an exponential increase in the production of pomegranate products ( Argov-Argaman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several research studies, published in the last 20 years ( Singh et al, 2023 ), highlighted that the fruit of the pomegranate, Punica granatum L. , possesses various pharmacological properties including antioxidant, anti-inflammatory, anti-cancer, and antimicrobial activities. Furthermore, PPE is a nutrient by-product of the fruit that is becoming abundant due to an exponential increase in the production of pomegranate products ( Argov-Argaman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the PPEs were not toxic to fibroblasts treated with all the tested concentrations of PPEs. Multiple studies reported that the tropical application of PPE induced the wound healing via promotion of collagen production and stimulation of several growth factors (Singh et al., 2023 ). Further clinical studies can be helpful to assess the potential of different PPEs to heal wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The displayed antibacterial activity was against a group of Gram‐positive and Gram‐negative bacteria including Escherichia coli , Listeria monocytogenes (Belgacem et al., 2020 ), Pseudomonas aeruginosa , Staphylococcus aureus , Salmonella and Bacillus spp., Vibrio parahaemolyticus , Clostridia , and Yersinia enterocolitica (Akhtar et al., 2015 ; Sorrenti et al., 2019 ; Wu et al., 2018 ). Despite the many extraction techniques used to highlight the importance of pomegranate peel as a source of bioactive compounds for industrial uses, collective findings are inconsistent due to the lack of standardized methodologies for extracting the most effective bioactive materials (Singh et al., 2023 ). This makes it difficult to assess the sufficient and safe use of pomegranate peel in industrial applications, especially those relevant to food preservations and pharmaceutical uses.…”
Section: Introductionmentioning
confidence: 99%
“…Punicalagin, a polyphenol found in the peel of the pomegranate ( Punica granatum L. ), is a natural compound capable of exerting anti-inflammatory, cardioprotective, neuroprotective, wound healing, antimicrobial and anticancer properties. This bioactive compound develops its multiple pharmacological effects mainly through its antioxidant activity ( Singh et al, 2023 ). In a recent paper, punicalagin was delivered to the mouse brain using an intracranially injectable therapeutic hydrogel ( Ju et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%